Surgical Management of a Misdiagnosed Completely Thrombosed Giant Cerebral Aneurysm Mimicking a Cystic Echinococcosis - Chihi, Mehdi; Sure, Ulrich (Current Practice in Medical Science Vol. 11, 2022)
Completely thrombosed giant cerebral aneurysms are rare lesions that could sometimes be misdiagnosed due to atypical radiographic features. Huge spherical intracerebral masses must be kept in mind in every case as a differential diagnosis to guarantee the best surgical approach and resection of the lesion. In this rare case, we show that even technologically developed imaging could not accurately diagnose this rare entity and enable preoperative surgical planning. This case also reveals how important is the surgical management of these lesions when surgery is performed in a high-volume neurosurgical vascular center by an experienced vascular neurosurgeon.